Degenerações periféricas da retina em pacientes candidatos à cirurgia refrativa - Morales, Paulo Henrique de Avila [UNIFESP] (2001)
Purpose: To verify, in myopic individuals who are candidates for refractive surgery, the prevalence of different types of peripheral degenerative lesions of the retina, according to the type of myopia. Methods: Prospectively, during a one-year interval, we examined the eyes of patients in the Refractive Surgery Sector of the Department of Ophthalmology of the Federal University of São Paulo - Paulista School of Medicine, who presented at the initial visit a refraction with spherical equivalent above or equal to -1.00 spherical diopter, and did not have a personal background of ocular disease or surgery in that period. We investigated the existence of lesions and/or peripheral degeneration, which predispose to rhegmatogenous detachment of the retina. Results: The group was mostly composed of young adults (average age 31). We observed eyes with low myopia (263 eyes, 31%), moderate myopia (300 eyes, 36%) and high myopia (277 eyes, 33%). In 35.4% of the patients (27% of the eyes) we found peripheral degeneration, and the white with or without pressure was the most frequent finding (23.4% of the patients or 17.5% of the eyes). Among the lesions that predispose to rhegmatogenous detachment of the retina, the most frequently found was the lattice degeneration (8.6% of the patients or 6% of the eyes). Conclusions: The peripheral alterations which predispose or not to rhegmatogenous detachment of the retina presented an increase in prevalence according to the increase in the myopia grade, with the exception of tears. All patients with high myopia and candidates for refractive surgery should have the retinal periphery of both eyes examined.